Characterization and comparation test of chicken eggs strain isa brown and hyline brown in different areas - Setiawan Hakim; Yusuf Leonard Henuk; Hamdan .; Iskandar Sembiring; Hasnudi . (Universitas Sumatera Utara, 2017)
This study aims to determine the characterization and comparative test of exterior and interior qualities including egg weight, eggshell thickness, egg shape, air cavity and interior including high albumin, egg yolk, and haugh egg unit from egg strain Isa Brown and Hyline Brown in different areas of Deli Serdang and Langkat regencies, North Sumatra Province in June-July 2017. The eggs used in this study were 400 eggs divided by 100 Isa Brown and 100 Hyline Brown from Denai Village, Pantai Labu Subdistrict, Regency Deli Serdang, then 100 Isa Brown and 100 Hyline Brown from Sei Limbat Village, Kecamatan Selesai, Langkat District. Each egg is collected directly from the chicken and then measured against the exterior and interior. The results showed that the characterization and comparative test of chicken eggs consumption of strains of Isa Brown and Hyline Brown in different regions had results(thit> ttable) with t test on comparative test I1: H1 and I2: H2 meaning egg of different strain showed different result also on egg weight parameter, shapeegg, shell weight, air cavity, egg white index, haugh unit, egg yolk index and yolk color. The comparative test I1: I2 showed no significant differences (thit <ttabel) on egg weight, shell thickness, shell weight, egg white index, haugh unit and egg yolk index, but showed significantly different (titable) results in egg shape, air cavity and yolk color, meaning there is environmental influence but not significant to other quality of egg with same strain in different region. In the H1: H2 comparative test the results were not significantly different (thit <ttabel) on all parameters except the color of egg yolks, meaning that no environmental or strain effect produced eggs of the same quality in different regions.